Representações Sociais de três gerações acerca da ditadura Militar e da comissão da verdade - Delfino, Elluênia Lucena Claudino (2014)
In 2012 the national truth commission in Brazil was sanctioned to work for two years, with the objective of investigating human rights violations and appointing the people responsible for killings, torture and disappearances during the military regime. In 2014, on the 50th anniversary of this period, the committee should release reports. In this context, the study has the general objective of analyzing the social representations of three generations regarding the military dictatorship, as well as the opinion of these people about the truth commission. The sample is comprised of 209 participants. Data was analyzed by the Evoc program, from the expression “Governo Militar”. The core of the representation showed that the introduced contents are strongly attached to a negative action (repression) associated with the government structure of "dictatorship". The data was also analyzed by Alceste software. The results indicate the formation of 5 classes, with Class 2, "Investigation of Human Rights Violations by the Commission of Truth", being the most representative of the group. Taken together, the results demonstrate the importance of the subject for the participants. It also leads to the perception that the rescue of historical memories influence the representations anchored overtime by those who have lived and/or listened to facts of this period, such as killings, torture and political disappearances.